Crystal Structure of Phototoxic Orange Fluorescent Proteins with a Tryptophan-Based Chromophore. - Nadya V Pletneva; Vladimir Z Pletnev; Karen S Sarkisyan; Dmitry A Gorbachev; Evgeny S Egorov; Alexander S Mishin; Konstantin A Lukyanov; Zbigniew Dauter; Sergei Pletnev (PLoS ONE)
Phototoxic fluorescent proteins represent a sparse group of genetically encoded photosensitizers that could be used for precise light-induced inactivation of target proteins, DNA damage, and cell killing. Only two such GFP-based fluorescent proteins (FPs), KillerRed and its monomeric variant SuperNova, were described up to date. Here, we present a crystallographic study of their two orange successors, dimeric KillerOrange and monomeric mKillerOrange, at 1.81 and 1.57 Å resolution, respectively. They are the first orange-emitting protein photosensitizers with a tryptophan-based chromophore (Gln65-Trp66-Gly67). Same as their red progenitors, both orange photosensitizers have a water-filled channel connecting the chromophore to the β-barrel exterior and enabling transport of ROS. In both proteins, Trp66 of the chromophore adopts an unusual trans-cis conformation stabilized by H-bond with the nearby Gln159. This trans-cis conformation along with the water channel was shown to be a key structural feature providing bright orange emission and phototoxicity of both examined orange photosensitizers.